A high interferon gamma signature of CD8+ T cells predicts response to neoadjuvant immunotherapy plus chemotherapy in gastric cancer - Li, Sen; Li, Ke; Tian, Fei; Li, Hongle; Xia, Qingxin; Li, Tiepeng; Dong, Bing; Li, Danyang; Yu, Juan; Zhang, Junli; Wang, Li; Zhang, Chengjuan; et al. (Frontiers in Immunology, 2023)
While the tumor microenvironment (TME) affects immune checkpoint blockade (ICB) efficacy, ICB also reshapes the characteristics of TME. Thus far, studies have focused on the TME evolution during neoadjuvant or adjuvant ICB therapy in gastric cancer (GC). However, the interaction between TME characteristics and neoadjuvant immunotherapy plus chemotherapy remains to be elucidated. We performed single-cell RNA sequencing on ten GC specimens pre- and post-neoadjuvant camrelizumab plus mFOLFOX6 to determine the impact of the TME on the efficacy of the combination therapy and the remodeling of TME by the therapy. A high baseline interferon gamma (IFN-γ) signature in CD8+ T cells predicts better responses to the combination therapy. We also observed that the IFN-γ signature significantly decreased in multiple cell types, and the exhausted signature of CD8+ T cells was significantly suppressed during the neoadjuvant therapy. Moreover, intracellular interactions between CD8+ T cells and epithelium or macrophages were remodeled by the neoadjuvant therapy. Our data reveal interactions between the TME and neoadjuvant immunotherapy plus chemotherapy in GC. Importantly, it also highlights the signature of CD8+ T cells in predicting response to the combination therapy in GC.